Dual-axis solar tracker system utilizing Fresnel lens for web-based monitoring - Ayu, Humairoh Ratu; Kurniawansyah, Rifki Mohamad; Supriyanto, Amir; Junaidi, Junaidi (Institute of Advanced Engineering and Science, 2024)
Solar energy produced using solar panels is a renewable source of electricity. Over the years, several studies have been developed in the field to increase the performance efficiency of these panels. Therefore, this study aims to develop dual-axis solar tracker with the addition of Fresnel lens to improve performance efficiency. The system implemented consisted of multisensors, servo motors, Fresnel lenses, Arduino nano, and NodeMCU ESP32. In the experiments, proposed tracking system with and without Fresnel lens were evaluated to compare the output of both setups. The results showed that the maximum power of dual-axis solar tracker with and without the device was 13.60 W and 15.78 W, respectively, at the same radiation intensity, temperature, and time. These findings showed that the proposed tracking system could increase the maximum power efficiency of solar panels by 16.03%. Furthermore, the maximum value was obtained when dual-axis solar tracker with Fresnel lens moved from E to W at 23° to the horizontal.